(untitled) (XXI Century. Spanish Literature and Culture, 2020)
This article studies Enrique Vila-Matas’ Doctor Pasavento (2005), focusing on its main character: a traveler suffering from a severe identity crisis, and mixed in tangled texts, which protect him while dispersing him. The novel picks up, embodied in its unstable hero, on some posmodernity keys within the literary space. Pasavento runs away, disintegrates and reconstructs uncontrollable, without hope of returning.